A novel bearingless interior permanent magnet slice motor driven blood pump. (April 2023) - Kant, Krishan; Weinreb, Benjamin S.; Hegy, Michael; Speakman, Jeff; Gartner, Mark; Trumper, David L.
Abstract: A 2-pole bearingless interior permanent magnet (IPM) motor with slice rotor configuration is presented in this paper. A novel IPM rotor is designed considering direct and indirect operational specifications such as force constant, torque constant, axial/radial stiffness and cogging torque. Cogging torque and its resulting vibrations affect motor and levitation operation significantly. Hence, various rotor configurations are simulated using the finite element method to develop a topology that minimizes these phenomena. The final topology is tested for closed-loop levitation and speed control. The motor is also tested for its intended application as a blood pump. A mock circulatory loop is developed to measure the performance of the pump. The simulation results, experimental control system performance and pump performance results are shown and explained in the paper. Graphical abstract: